2017
DOI: 10.1016/j.cej.2016.11.126
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of growth media on the monitoring of E. coli inactivation and regrowth after solar and photo-Fenton treatment

Abstract: This study intends to assess the cultivability of photo-treated Escherichia coli K-12 on media with different selectivity (PCA, LBA, T-7, T-7+TTC, VRBA and MAC) and to establish optimal conditions for bacterial recuperation. For these purposes, immediate and long-term bacterial recovery after SODIS and photo-Fenton are evaluated. Moreover, the use of catalase and sodium pyruvate supplements in the medium is studied. The non-selective medium PCA showed the highest counts for the untreated and treated cells due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…In laboratory experiments with E. coli simulating disinfection with SODIS and photo-Fenton (see Section 10.3), no recovery or regrowth was observed, although cells retained culturability longer on less selective media. 167 Using microcosm experiments, Ent. faecalis appeared to become permanently inactivated by sunlight in clear seawater and not to experience repairable injuries within 48 h, 127 similar to ndings of others on Salmonella and Shigella.…”
Section: Damage Versus Inactivationmentioning
confidence: 99%
“…In laboratory experiments with E. coli simulating disinfection with SODIS and photo-Fenton (see Section 10.3), no recovery or regrowth was observed, although cells retained culturability longer on less selective media. 167 Using microcosm experiments, Ent. faecalis appeared to become permanently inactivated by sunlight in clear seawater and not to experience repairable injuries within 48 h, 127 similar to ndings of others on Salmonella and Shigella.…”
Section: Damage Versus Inactivationmentioning
confidence: 99%
“…Different studies have confirmed the effect of high temperature resulting from solar exposure on different water microorganisms, especially its synergistic effect with UV radiation that comes with solar radiation, which accelerates the disinfection process [39]. The short wavelengths of UVB (280-320 nm) are highly absorbable by the nucleic acid of living organisms within the water, causing severe damage in the genetic material and eventually causing their disinfection [40]. Numerous investigations have recently been conducted to confirm the ability and the mechanisms of sunlight to inactivate different standard microorganisms including bacteria, viruses, and fungi, in addition to protozoa and some helminths [3,[41][42][43].…”
Section: Mechanisms Of Solar Disinfectionmentioning
confidence: 99%
“…Application of heterogeneous photocatalysis for disinfection was reported at first in 1988 by Matsunaga et al, who employed TiO 2 to inactivate L. acidophilus, S. cerevisiae, and E. coli. Since then, photocatalysis has been largely applied in disinfection systems, and the gram-negative bacteria E. coli is by far the most studied organism in these applications since it is an indicator of fecal contamination in water, non-pathogenic to humans, and it is easily cultivated in academic laboratories [85]. Similarly, due to its elevated stability, high efficiency, and low toxicity, TiO 2 is the most investigated semiconductor in disinfection systems.…”
Section: Photocatalytic Disinfectionmentioning
confidence: 99%
“…These components include phospholipids and lipo-polysaccharides that, in the case of E. coli, have been proven to react directly with the h þ vb of TiO 2 [90,91]. Other damages inflicted to cell structures can be caused by the exposure to radiation directly in the DNA structure that happens mostly in the UVC range of the solar spectrum, and also by ROS formed during photocatalysis-especially the HO • [92]-or during the interaction of radiation and specific intracellular structures [71,85]. The inactivation mechanism in photocatalytic processes is therefore extremely complex and includes several steps resulting not only from the presence of a photocatalyst but also from the irradiation itself.…”
Section: Photocatalytic Disinfectionmentioning
confidence: 99%